Analisis Struktur Jumlah Sel Darah untuk Pembelajaran pada Mahasiswa Farmasi - Indah Maisyarah Buliani; Ardi Mustakim (Jurnal Cakrawala Pendidikan dan Biologi, 2025)
This research aims to analyze the summation of blood cells so that it becomes a reference for pharmacy students in their learning and becomes the foundation for further study of pathology, pharmacology, and therapeutic mechanisms that they can use in professional practice. This study uses qualitative research, primary data sources and secondary data sources generated from literature studies, data types in the form of qualitative, data collection techniques in the form of tracing previous research, data analysis techniques in the form of qualitative descriptive. Blood is one of the organs in the human body that is very vital. Blood is a unit consisting of blood cells and blood plasma. This analysis is carried out to obtain information about the sum of blood cells in the human body, hospitals or laboratories conduct blood analysis with excellent accuracy but the shortcomings lie in the slow process and the accuracy becomes non-standardized because it depends on the level of expertise/experience of the operator and also the level of fatigue. Efforts to overcome the length of time and for the purpose of initial diagnosis can use image processing techniques based on blood cell morphology. Along with the development of technology, there are currently several researchers who are conducting various studies in the application of computerized methods used in the classification of white blood cell types. The main function of red blood cells is to carry oxygen from the lungs and distribute it throughout the body. The analysis of human blood is very important, especially related to the diagnosis of a disease. Based on the results of this study, it shows how many red blood cells are present in the body and can be applied to detect a disease. For pharmacy students, an understanding of the sum of blood cells is necessary to develop knowledge and will be useful in clinical practice.